2015
DOI: 10.1121/1.4935518
|View full text |Cite
|
Sign up to set email alerts
|

Whistle characteristics of the spinner dolphin population in the Comoros Archipelago

Abstract: Observed variations in dolphin acoustic signals may be associated with behavior, social composition, and local differences in habitat features. This study aims at characterizing whistles emitted by the spinner dolphin population occurring in the waters of the main island of the Archipelago of Comoros (Mozambique Channel, Indian Ocean) and to assess factors possibly influencing the acoustic structure of signals. All parameters examined on 953 whistles significantly differed in relation to environmental conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…These variations can also be influenced by species‐specific differences in repertoire or environmental factors within the local habitat (May‐Collado and Wartzok ; Bonato et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…These variations can also be influenced by species‐specific differences in repertoire or environmental factors within the local habitat (May‐Collado and Wartzok ; Bonato et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…There are no published sound recordings from Australia. Their sounds have instead been document from Hawaii [230,[256][257][258][259][260][261][262], the Eastern Tropical Pacific [151,152], the northwestern Atlantic [174], Brazil [263][264][265] and the western Indian Ocean off Madagascar [266].…”
Section: Stenella Longirostris-long-snouted Spinner Dolphinmentioning
confidence: 99%
“…Therefore, frequency parameters may be distinctive in local populations and reflect certain habitat characteristics in each area (Bonato et al . ). This phenomenon was first proposed by Morton () as the “Acoustic Adaptation Hypothesis (AAH),” which predicts that habitat presents selective forces favoring the evolution of some sound aspects over others.…”
Section: Discussionmentioning
confidence: 97%
“…Bonato et al . () showed that the frequency parameters of spinner dolphin S. longirostris whistles were related only to habitat‐dependent variables (wind/sea conditions and depth) in the Comoros Archipelago, suggesting that this is the result of environmental selection on acoustic signals in this species. Louzada () emphasizes that the large behavioral repertoire of Guiana dolphins is the result of evolutionary processes driven by environmental heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation